a(fog)

we put x= g(x)

f(g(x)) = 2(x+4/2x-5)-1 / (x+4/2x-5) -2

=(2x+8/2x-5)-1 / (x+4/2x-5) -2

taking lcm and solving

=2x+8-2x+5/(2x-5) / x+4-4x+10(2x+5)

=13/-3x+14

fog = 13/14-3x

b) gof

we put x=(fx) in gx

g(f(x)) = (2x-1/x-2 +4 ) / 2(2x-1/x-2 -5)

by taking lcm and solving

= 2x-1+4x-8/(x-2) / 4x-2-5x+10/(x-2)

gof=6x-9/-x+8

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up